Analysis of performance differences between medalist and non-medallist players in elite women`s badminton - Gomez, M.-A.; Rivas, F.; Ruis, L.-M.; Cid, A. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The analysis of player`s performance in elite badminton has been widely investigated differentiating by gender, group stages during championships, winners and losers, or best vs. worst players (Barreira et al.. 2016; Chiminazzo et al.. 2018). However, the analysis of key variables that may define the success to gain a medal or not during an International Championship is still inconclusive in elite women's badminton. Therefore, the aim of the present study was to identify the differences between medallists and nonmedallists players` performance (temporal and notational variables) in elite women`s badminton. Methods: The sample was composed by 18 matches played by the medallists from the 2016 women`s singles Olympic Games (Rio. Brazil). The final sample included the analysis of 1,340 rallies. The independent variable studied was medallist/non-medallist; while the dependent variables were serve type, point outcome (winner, forced error or unforced error) according to the complex of game (C1: serving and C2: receiving) and temporal variables (rally time, rest time, density and frequency of strokes). The analyses were carried out using an observation tool on a video analysis program (Dartfish. Friburgo. Switzerland). The crosstabs commands were used to study the relationships (Pearson's Chi-square test) between medallist/non-medallist condition and point outcome and type of serve. The student t-test was applied to differentiate medallist conditions of temporal variables. Results: The temporal variables studied showed that only rest time was different for medallist players with more time spent after the rally (29.88s vs 26.77s). Rally time, density and frequency of strokes was non-significant differentiating both conditions (p>0.05). In addition, the medallists obtained more points when serving than non-medallist (greater winners and more unforced errors from the opponent). Conversely, the non-medallists performed better when received due to more forced and unforced errors from the opponent. Lastly, the type of service was different in both players (medallists and nonmedallist) with medallists using more backhand short service and non-medallists using more forehand short service. Conclusions: The performance of medallists and non-medallists women's badminton players is different from a temporal (rest time spent) and a notational analysis perspective (points obtained when serving the medallists and when receiving the non-medallists).